Power test of a paddle wheel wind-mill - Pincomb, Charles Edwin (My University, 1896)
Introduction: The machine used in this test was one built at the Kansas State Agricultural College mechanical Department, by the students under the direction of Prof. OP Hood in charge. It was built throughout of rough material without castings, as it was desired to make a machine similar to those commonly built by the farmers of western Kansas who use them for irrigating.
Citation: Pincomb, Charles Edwin. Power test of a paddle wheel wind-mill. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Kansas State Agricultural College; Kansas farmers; Paddle wheel wind-mill; Theses; Manuscripts (documents)